2024
DOI: 10.1038/s44161-024-00429-9
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 protects from atherosclerosis by limiting necrotic core formation

Marie Piollet,
Florentina Porsch,
Giuseppe Rizzo
et al.

Abstract: Atherosclerosis is a chronic disease of the vascular wall driven by lipid accumulation and inflammation in the intimal layer of arteries, and its main complications—myocardial infarction and stroke—are the leading cause of mortality worldwide1,2. Recent studies have identified triggering receptor expressed on myeloid cells 2 (TREM2), a lipid-sensing receptor regulating myeloid cell functions3, to be highly expressed in macrophage foam cells in experimental and human atherosclerosis4. However, the role of TREM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In line with the protective role of LAMs, several authors reported that following HFD, depletion TREM2 + LAM exacerbates WAT dysfunction and metabolic abnormalities (Jaitin et al, 2019). Remarkably, TREM2 + LAMs exert a protective role in other metabolically-stressed tissues such as the heart (Piollet et al, 2024;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 81%
“…In line with the protective role of LAMs, several authors reported that following HFD, depletion TREM2 + LAM exacerbates WAT dysfunction and metabolic abnormalities (Jaitin et al, 2019). Remarkably, TREM2 + LAMs exert a protective role in other metabolically-stressed tissues such as the heart (Piollet et al, 2024;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 81%
“…26 However, in advanced plaques, whole-body Trem2 deletion led to increased necrotic core formation due to impaired efferocytosis and excess cell death. 27 Overall, these data suggest that while inhibiting Trem2 during early lesion development may slow disease progression, promoting Trem2 signaling in advanced disease could impair necrotic core formation and plaque inflammation to promote stability.…”
mentioning
confidence: 77%
“…This conclusion is further supported by a recent report investigating germline Trem2 deletion in advanced atherosclerotic plaques that found while Trem2 deletion had no effect on plaque size, Trem2deficient mice had larger necrotic cores. 27 It has been proposed that the effect of macrophage cell death on plaque outcomes depends on the stage of plaque development. 39,40 Thus, we hypothesize that while promoting foamy macrophage cell death by inhibiting Trem2 during early atheroma development may slow progression, agonizing Trem2 in advanced lesions may be more important to promote plaque stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TREM2 + cells have been shown to have beneficial properties in hepatic and renal tissue damage, but blockade of these cells restores anti-tumor immunity [58][59][60][61] . There is evidence for both pro-and anti-atherosclerotic properties of TREM2 33,62 , and it remains possible that lipid-loaded macrophages have a role in restraining inflammation via PPAR 63 . In the tumor microenvironment, lipid-loading in tumor-associated macrophages decreases phagocytosis and increases PD-L1 expression, resulting in an immunosuppressive environment for tumor growth 17 .…”
Section: Discussionmentioning
confidence: 99%